Alpha(2)-adrenergic activation in the lateral parabrachial nucleus induces NaCi intake under conditions of systemic hyperosmolarity - Andrade, Carina Aparecida Fabrício de [UNESP]; De Luca, L. A.; Colombari, Débora Simões de Almeida [UNESP]; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2006)
The inhibition of sodium intake by increased plasma osmolarity may depend on inhibitory mechanisms present in the lateral parabrachial nucleus. Activation of alpha(2)-adrenergic receptors in the lateral parabrachial nucleus is suggested to deactivate inhibitory mechanisms present in this area increasing fluid depletion-induced 0.3 M NaCl intake. Considering the possibility that lateral parabrachial nucleus inhibitory mechanisms are activated and restrain sodium intake in animals with increased plasma osmolarity, in the present study we investigated the effects on water and 0.3 M NaCl intake produced by the activation of alpha(2)-adrenergic receptors in the lateral parabrachial nucleus in rats with increased plasma osmolarity. Male Holtzman rats with stainless steel cannulas implanted bilaterally into the lateral parabrachial nucleus were used. One hour after intragastric 2 M NaCl load (2 ml), bilateral injections of moxonidine (alpha(2)-adrenergic/imidazoline receptor agonist, 0.5 nmol/0.2 mu l, n=10) into the lateral parabrachial nucleus induced a strong ingestion of 0.3 M NaCl intake (19.1 +/- 5.5 ml/2 h vs. vehicle: 1.8 +/- 0.6 ml/2 h), without changing water intake (15.8 +/- 3.0 ml/2 h vs. vehicle: 9.3 +/- 2.0 ml/2 h). However, moxonidine into the lateral parabrachial nucleus in satiated rats not treated with 2 M NaCl produced no change on 0.3 M NaCl intake. The pre-treatment with RX 821002 (alpha(2)-adrenergic receptor antagonist, 20 nmol/0.2 mu l) into the lateral parabrachial nucleus almost abolished the effects of moxonidine on 0.3 M NaCl intake (4.7 +/- 3.4 ml/2 h). The present results suggest that alpha(2)-adrenergic receptor activation in the lateral parabrachial nucleus blocks inhibitory mechanisms, thereby allowing ingestion of hypertonic NaCl under conditions of extracellular hyperosmolarity. We suggest that during cell dehydration, circuits subserving sodium appetite are activated, but at the same time strongly inhibited through the lateral parabrachial nucleus. (c) 2006 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: sodium appetite; thirst; moxonidine; osmoreceptor; dehydration